Assessment of Infant Feeding Attitudes of a Group of Women who Attended Prenatal Education Class - Sahin, Sevil; Sevimli Guler, Dondu; Düzgün, Ayten; Unsal, Alaattin; Uslu Yuvacı, Hilal (Progress in Nutrition, 2021)
Objective: To determine infant feeding attitudes of a group of women who attended prenatal education class and to review some variables that are believed to be associated. Material and methods: Infant feeding attitudes of the mothers were assessed with the Iowa Infant Feeding Attitude Scale. Mann-Whitney U test and Kruskal-Wallis test were used for the analyses. Results: The scores obtained from the Iowa Infant Feeding Attitude Scale by the mothers ranged from 44 to 79 with a mean score of 65.55 ± 5.71. The women younger than 35 years of age, women whose spouse is 35 years old and older, those with a good family income, those who had postnatal breastfeeding education, those who breastfed their child within the first one hour after childbirth, those who exclusively feed their infant with breast milk for two months and longer, those who breastfed for a total of 12 months and longer, and those who started complementary feeding at 12 months of age and later had higher scores from the Iowa Infant Feeding Attitude Scale. Conclusion and suggestions: It can be suggested that a group of mothers who attended prenatal education class had positive infant feeding attitudes in our study.